How do you want your chatbot? An exploratory Wizard-of-Oz study with young, urban Indians - Thies, Indrani Medhi; O'Neill, Jacki; Menon, Nandita; Magapu, Sneha; Subramony, Manisha (INTERACT 2017, 2017)
As text-messaging chatbots become increasingly “human”, it will be important to understand the personal interactions that users are seeking with a chatbot. What chatbot personalities are most compelling to young, urban users in India? To explore this question, we first conducted exploratory Wizard-of-Oz (WoZ) studies with 14 users that simulated interactions with a hypothetical chatbot. We evaluated three personalities for the chatbot—Maya, a productivity oriented bot with nerd wit; Ada, a fun, flirtatious bot; and Evi, an emotional buddy bot. We followed up with one-on-one interviews with the users discussing their experiences with each of the chatbots, what they liked, and what they did not. Overall our results show that users wanted a chatbot like Maya, who could add value to their life while being a friend, by making useful recommendations. But they also wanted preferred traits of Ada and Evi infused into Maya.